Penetration resistance of a dystrophic Red-Yellow Latosol (Oxisol) under different managements and methods - Silva, Lucivânia Izidoro da; Campos, Milton César Costa; Wadt, Paulo Guilherme Salvador; Cunha, José Maurício da; Oliveira, Ivanildo Amorim de; Freitas, Ludmila de; Santos, Eduardo Antônio Neves dos; Brito Filho, Elilson Gomes de (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2020)
Soil management systems have a great influence on soil physical properties and are related to soil compaction. This work aimed to evaluate the soil mechanical resistance to penetration of a dystrophic Red-Yellow Latosol (Oxisol) under different management. The experiment was carried out at Embrapa Rondônia experimental field, in Porto Velho, RO, Brazil. Samples were collected for analysis at depths from 0 to 0.05; 0.05 to 0.10; and 0.10 to 0.20 m. The penetrometers used were: an electronic model MA-933 / Marconi, and an automated field, model SOLO TRACK / Falker. The treatments consisted of the absence and addition of 2000 kg ha -1 of agricultural plaster, absence and presence of soil scarification, and three crop succession systems: SP (soybean / fallow), SMP (soybean / corn / fallow) and SMBP (soybean / maize / brachiaria / fallow). The experimental design was in randomized blocks, in a 2x2x3 factorial scheme with eight blocks. Data were subjected to analysis of variance, and when significance was found, means were compared by the Scott-Knott test at the 5% probability level. Crop succession systems can influence soil physical characteristics, the lowest PR values were observed in SMBP and SMP succession systems. The MA-933 was better to evaluate of mechanical penetration resistance.